Paul: The Answer to the Riddle of As For Me and My House - Mitchell, Barbara (Studies in Canadian Literature, 1988)
The character of Paul in Sinclair Ross’ As For Me and My House has been dismissed by critics as "pedantic" and "supercilious." However, like Lewis Carroll (whom he cites), he actually has a double identity as scholar/teacher and fool/poet. Paul rejuvenates Mrs. Bentley’s capacity for love and for creativity, and so he is the restorer of the Bentleys’ crumbling marriage. His presence and his frequent philological games always token a turning point in the narrative, or a crisis in the subtle sensual relationships between the other characters. He is the central agent to both plot and character development.